1994
DOI: 10.1677/joe.0.1400349
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thyroid hormone on androgen metabolism in peripuberal rat Sertoli cells

Abstract: The aim of the present study was to investigate the influence of thyroid hormones on androgen metabolism in Sertoli cells isolated from 3- and 4- week-old rats. Hypothyroidism was induced by the oral administration of 0.025% methimazole (MMI) from birth until the rats were killed at 3 and 4 weeks of age. Half of the MMI-treated animals were injected i.p. with L-triiodothyronine (T3 3 micrograms/100 g body weight) during the last week before death. Sertoli cells from all groups were initially cultured under bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 0 publications
3
25
0
Order By: Relevance
“…The quantum of oestradiol secretion by Leydig cells stimulated with T3 suggest that Leydig cell aromatase activity is more sensitive to thyroid hormones rather than LH. T3 inhibits the Sertoli cell aromatase activity and granulosa cell aromatase mRNA [41][42][43], whereas it stimulates the production of oestradiol in Leydig cells, suggesting cell specific differential role of thyroid hormones on testicular oestradiol production.…”
Section: Discussionmentioning
confidence: 97%
“…The quantum of oestradiol secretion by Leydig cells stimulated with T3 suggest that Leydig cell aromatase activity is more sensitive to thyroid hormones rather than LH. T3 inhibits the Sertoli cell aromatase activity and granulosa cell aromatase mRNA [41][42][43], whereas it stimulates the production of oestradiol in Leydig cells, suggesting cell specific differential role of thyroid hormones on testicular oestradiol production.…”
Section: Discussionmentioning
confidence: 97%
“…This could very well have postponed the formation of Leydig cell progenitors from stem Leydig cells. Furthermore, several in vitro and in vivo studies have shown that the active thyroid hormone T 3 can directly influence Sertoli cell proliferation and function such as aromatase activity (34,48), androgen metabolism (35), and IGF-I production (33). The Sertoli cells in their turn have been reported to influence the formation of the adult-type Leydig cell population (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The prolonged proliferation phase observed in immature Sertoli cells prepared from hypothyroid rats was associated with an increase in thyroid receptors (Palmero et al 1993), a dramatic enhancement of aromatase activity (Panno et al 1994) and increased estrogen-receptor content (Panno et al 1996b). Hormone replacement (with T 3 ) markedly shortened Sertoli cell replication (van Haaster et al 1993) and dramatically reduced both aromatase activity (Panno et al 1996b) and estrogen-receptor content (Panno et al 1996a).…”
Section: Introductionmentioning
confidence: 98%